Kajian Literatur: Instagram sebagai Media Ekspresi Keagamaan - Marzal, Novrizon; Truna, Dody S.; Albustomi, Ahmad Gibson (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
The internet has mushroomed around the world, including Indonesia. Based on data, 78.19% of Indonesia's population is connected to the internet and the highest access is used for social media. One of the social media that is consistently used is Instagram, Instagram is ranked second as the most popular social media platform. Using the literature review method and a thematic approach, this article focuses on the concepts of digital religion, algorithms, media literacy, and theology in the context of Instagram. This article discusses the use of Instagram as a medium to express religious identity in the digital era. Instagram, which was initially used as a moment-sharing platform, has evolved into a means of disseminating religious information. The article examines the relationship between religion and digital technology, highlighting how Instagram algorithms influence religious expression and shape users' identities. The author emphasises the importance of media literacy to avoid negative impacts such as hoaxes and the normalisation of deviant religious practices. In conclusion, Instagram provides new opportunities and challenges for religious expression, and it is important for religious authorities to engage actively and creatively in using this medium.